Association between vitamin D status and cardiometabolic risk factors in adults with type 2 diabetes in Shenzhen, China - Liu, Yan-Jing; Duan, Jing-Wen; Lu, Dong-Hui; Zhang, Fan; Liu, Hong-Li (Frontiers in Endocrinology, 2024)
Background: Evidence of vitamin D status and cardiometabolic health in adults with type 2 diabetes mellitus (T2DM) is still limited. This study aimed to investigate the association between vitamin D status and cardiometabolic risk factors in adult T2DM patients in Shenzhen, China. Methods: This cross-sectional study included 164 adults (aged ≥18 years) with T2DM who were hospitalized at Peking University Shenzhen Hospital from March 1, 2023, to May 31, 2023. Serum 25-hydroxyvitamin D [25(OH)D] concentration, the active marker of vitamin D, and three major cardiometabolic risk factors including blood pressure (BP), glucose metabolism-related indicators, and blood lipid profiles were collected. Vitamin D deficiency (VDD) was defined as 25(OH)D < 20 ng/mL. Correlation, Regression, and Logistic analysis were applied to verify the association among serum 25(OH)D concentration, VDD, and 11 cardiometabolic risk factors. Results: Median 25(OH)D concentration was 21.78 (IQR=17.51-28.05) ng/mL. The prevalence of VDD was 40.24%. Serum 25(OH)D concentration was significantly negatively correlated with diastolic BP (DBP) and HbA1c rather than systolic BP, plasma glucose, plasma C-peptide, and blood lipid profiles in adult T2DM patients in both correlation and linear regression analysis. Furthermore, the adjusted odd ratio for poor DBP control (≥90 mmHg) of T2DM patients with VDD was 3.164 (95% confidence interval=1.303, 7.683; P=0.011) compared to those without VDD. Conclusions: In China, VDD was highly prevalent in adult T2DM patients and associated with greater cardiovascular risk factors, especially with increased chances of uncontrolled DBP. These findings suggest that vitamin D levels should be monitored in T2DM patients, especially those with high DBP.